PENGARUH PEMBELAJARAN DARING TERHADAP TINGKAT PEMAHAMAN MAHASISWA ANGKATAN 2019 PRODI PENDIDIKAN BAHASA JEPANG FKIP UNRI PADA POLA KALIMAT なくてはならない/いけない、なくてもかまわない、DAN なくちゃ/なきゃ{いけない} - Era Fitri Ningsih; Nana Rahayu; Hermandra Hermandra (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2022)
Abstract: This research aimed to describe the effect of online learning on the level of student understanding of the and sentence patterns なくてはならない/いけない、なくてもかまわない、dan なくちゃ/なきゃ {いけない}. This research uses correlational method with a quantitative approach. The population and sampel of this study were student of the class of 2019 Japanese Language Education Study Program. The sample selected by using the census method. Data collextion in this study used a questionnaire and test instrument which was responded to by 32 respondents. The data in this study were processed with the help of IBM SPSS 25.0 by means of correlation analysis and regression analysis. From the result of the research obtained, it shows that there is a positive and significant relationship between online learning and the level of understanding of student in the class of 2019 of 31% with moderate correlation.Key Word: The effect, Online Learning, The comprehension of student